Regeneration and Agrobacterium-mediated transformation of cucumber [Cucumis sativus] and muskmelon [Cucumis melo] - Ramlan Saimat (Faculty of Food Science and Biotechnology,UPM, 2013)
Regeneration and Agrobacterium-mediated of cucumber (Cucumis sativus) and muskmelon (Cucumis melo L.), two of the more important commercial crop from the Family Cucurbitaceae were studied. The use of silver nitrate and cobalt chloride, inhibitors of ethylene action and biosynthesis respectively, was investigated on cucumber cv. Spring Swallow (SS) and Tasty Green (TG) and muskmelon cv. Birdie for their ability to enhance in vitro shoot regeneration. Poor regeneration was obtained, cotyledon and hypocotyl explants placed on a medium containing Murashige and Skoog (MS) medium and different concentrations BAP. In contrast, the percentage of shoot regeneration as well as number of shoots per explants increased when silver nitrate and cobalt chloride were added to the medium. For the transformation studies, explants were co-cultured with Agrobacterium tumefaciens strain LBA4404 separately carrying plasmids pBI121 and pKTY03 containing CaMV 35S promoter and PAL promoter respectively with kanamycin resistance and GUS gene. Putative transgenic cucumber plants regenerated directly from cells of the explants (leaf disc, petiole, cotyledon, and hypocotyl). Kanamycin-resistant plants regenerated 3 to 4 weeks after transferring onto selective medium